a) (y²-3y-5)(y²-3y+1)=-5
Пусть y²-3y = t, тогда
(t-5)(t+1) = -5
t²+t-5t-5+5=0
t²-4t=0
t(t-4)=0
t-4=0 ; t₂=0
t₁=4
Вернёмся к замене:
![\left \{ {{y^{2}-3y=0} \atop {y^{2} - 3y=4}} \right. \left \{ {{y^{2}-3y=0} \atop {y^{2} - 3y=4}} \right.](https://tex.z-dn.net/?f=%5Cleft%20%5C%7B%20%7B%7By%5E%7B2%7D-3y%3D0%7D%20%5Catop%20%7By%5E%7B2%7D%20-%203y%3D4%7D%7D%20%5Cright.)
1. y²-3y=0
y(y-3)=0
y-3=0 ; y₂=0
y₁=3
2. y²-3y=4
y²-3y-4=0
D = (-3)²-4*1*(-4)=9+16=25=5²
![y_{1} = \frac{3+5}{2*1} = \frac{8}{2} = 4 y_{1} = \frac{3+5}{2*1} = \frac{8}{2} = 4](https://tex.z-dn.net/?f=y_%7B1%7D%20%3D%20%5Cfrac%7B3%2B5%7D%7B2%2A1%7D%20%3D%20%5Cfrac%7B8%7D%7B2%7D%20%3D%204)
![y_{2} = \frac{3-5}{2*1} = - \frac{2}{2} = -1 y_{2} = \frac{3-5}{2*1} = - \frac{2}{2} = -1](https://tex.z-dn.net/?f=y_%7B2%7D%20%3D%20%5Cfrac%7B3-5%7D%7B2%2A1%7D%20%3D%20-%20%5Cfrac%7B2%7D%7B2%7D%20%3D%20-1)
Ответ: y₁ = ; y₂ =
б) ![\frac{y}{y+2} + \frac{y+2}{y-2} = \frac{8}{y^{2}-4 } \frac{y}{y+2} + \frac{y+2}{y-2} = \frac{8}{y^{2}-4 }](https://tex.z-dn.net/?f=%5Cfrac%7By%7D%7By%2B2%7D%20%2B%20%5Cfrac%7By%2B2%7D%7By-2%7D%20%3D%20%5Cfrac%7B8%7D%7By%5E%7B2%7D-4%20%7D)
y≠2 ;y≠-2
![\frac{y*(y-2)}{y+2} + \frac{(y+2)*(y+2)}{y-2} - \frac{8}{y^{2}-4 } =0 \frac{y*(y-2)}{y+2} + \frac{(y+2)*(y+2)}{y-2} - \frac{8}{y^{2}-4 } =0](https://tex.z-dn.net/?f=%5Cfrac%7By%2A%28y-2%29%7D%7By%2B2%7D%20%2B%20%5Cfrac%7B%28y%2B2%29%2A%28y%2B2%29%7D%7By-2%7D%20-%20%5Cfrac%7B8%7D%7By%5E%7B2%7D-4%20%7D%20%3D0)
![\frac{y^{2}-2y+y^{2}+4y+4 -8 }{y^{2}-4 } =0 \frac{y^{2}-2y+y^{2}+4y+4 -8 }{y^{2}-4 } =0](https://tex.z-dn.net/?f=%5Cfrac%7By%5E%7B2%7D-2y%2By%5E%7B2%7D%2B4y%2B4%20-8%20%7D%7By%5E%7B2%7D-4%20%7D%20%3D0)
![\frac{2y^{2} +2y-4 }{y^{2}-4 } =0 \frac{2y^{2} +2y-4 }{y^{2}-4 } =0](https://tex.z-dn.net/?f=%5Cfrac%7B2y%5E%7B2%7D%20%2B2y-4%20%7D%7By%5E%7B2%7D-4%20%7D%20%3D0)
![\frac{2(y^{2}+y-2) }{(y-2)(y+2)}=0 \frac{2(y^{2}+y-2) }{(y-2)(y+2)}=0](https://tex.z-dn.net/?f=%5Cfrac%7B2%28y%5E%7B2%7D%2By-2%29%20%7D%7B%28y-2%29%28y%2B2%29%7D%3D0)
![\frac{2(y-1)(y+2) }{(y-2)(y+2)}=0 \frac{2(y-1)(y+2) }{(y-2)(y+2)}=0](https://tex.z-dn.net/?f=%5Cfrac%7B2%28y-1%29%28y%2B2%29%20%7D%7B%28y-2%29%28y%2B2%29%7D%3D0)
| * (y-2)
2(y-1)=0
y-1=0
y=1
Отвeт: y=1